Analisis Fenomenologi Wartawan dalam Peliputan Program Citarum Harum - Ariani, Putri Restia; Wibawa, Darajat; Darsono, Dono (Annaba: Jurnal Ilmu Jurnalistik, 2024)
The purpose of this research is to determine the understanding of journalists from the Jurnalis Peduli Citarum Harum and Jurnalis Peduli Citarum communities in covering the Citarum Harum program, to determine the meaning of journalists from the Jurnalis Peduli Citarum Harum and Jurnalis Peduli Citarum communities in covering the Citarum Harum program, and to determine the experience of journalists from the Jurnalis Peduli Citarum Harum and Jurnalis Peduli Citarum communities in covering the Citarum Harum program. The results show an understanding of the coverage of the Citarum Harum program that includes environmental material, is guided by journalistic principles, and is carried out in a sustainable manner. The coverage of the Citarum Harum program is interpreted as coverage based on environmental awareness and program publication to the public. The experience of covering the Citarum Harum program includes the coverage strategy along with the difficulties, obstacles, and challenges experienced.